Kualitas Pelayanan Pendaftaran Rawat Jalan Pasien Jaminan Kesehatan Nasional di Rumah Sakit Royal Progress - Melly Susanti; Risky Kusuma Hartono; Desy Kartika Ningsih (CV. Syntax Corporation Indonesia, 2023)
The hospital is one of the health facilities where it organizes health efforts that deal with medical problems for the recovery and maintenance of health needed for its users. It is necessary to know the quality of outpatient registration services for National Health Insurance patients. To determine the effect of Input (HR, Technology Facilities) and processes (Professional and expertise, attitude, Behavior, Situation Control, Problem Solving, Ease of achievement and adjustment, Reliability and trust) that will produce quality in outpatient registration services at Royal Hospital Progress especially for patients using the National Health Insurance. sampling non-probability sampling. The sampling technique was purposive sampling. Human Resources, there is a shortage of service officers, in terms of internet speed technology and the lack of bridging of SIMRS with the JKN web is one of the factors that affect quality in terms of speed of service, in terms of the process where the ease of achieving and adjusting services has not been achieved because of the patient's waiting time when registering until data verification gets SEP still above 15 minutes. In other factors, namely Facilities, Professional and expertise, Attitude, Behavior, Control of the situation, Problem solving, Reliability and trust showed positive results. The quality of Outpatient Registration Services at the Royal Progress hospital illustrates good and satisfying service for patients including a very adequate waiting room, disabled toilets and elevators which are very much needed for patients. Registration staff are very professional in doing their jobs. Also described in the attitude of friendly and always smiling officers in receiving patients who come for treatment at Royal Progress Hospital, the very high empathy given by registration officers to patients who need help and the fast response received by patients when patients experience difficulties in administration This is what makes Royal Progress Hospital provide excellent service even though there is still a shortage of both human resources and networks, but in general the services provided to JKN patients are quite good